THE CONTRIBUTION OF SOIL CHEMICAL ATTRIBUTES GROWTH VEGETATIVE DEVELOPMENT OF PARICÁ IN DIFFERENT CULTIVED SYSTEMS - Rodrigues, Possidônio Guimarães (2016)
http://dx.doi.org/10.5902/1980509821091This study aimed to evaluate some chemical components of an Oxisol and the relationship with the vegetative development of paricá [Schizolobium amazonicum (Huber ex Ducke)] in different cropping systems in reforestation areas in the municipality of Tailandia, northeast paraense. Evaluated the PP [paricá x pueraria (Pueraria phaseoloides)], PA [paricá x acacia (Acacia mangium)] and P (monoculture paricá) systems conducted in 5 years by the company G.M. Sufredini Industrial LTDA and collected soil samples at a depth of 0-20 cm for analysis of pH, total C and N, H + Al, available P, exchangeable Ca, Mg, K and Al and calculated values ​​of C/N, SB, T, V and m. The vegetative development of paricá was assessed by survival, mortality and the number of defective plants beyond the DBH. The results showed that the increase in nitrogen content of the soil in PP treatment, the low soil fertility in PA treatment, but where paricá achieved the highest average in diameter (DBH = 16.64 cm) and greater survival rate in P treatment (90.63%). It was concluded that the soil-plant relationship in paricá and pueraria systems and monoculture paricá contributed to the establishment of individuals paricá.